Wheat Research Funding in Australia: The Rise of Public–Private–Producer Partnerships. (16th April 2013) - Alston, Julian M.; Gray, Richard S.
summary Wheat Research Funding in Australia: The Rise of Public–Private–Producer Partnerships The Australian wheat research system was transformed profoundly by three institutional innovations. First, in 1990 the Grains Research and Development Corporation (GRDC) was created to provide levy‐funded R&D. Second, in 1994 the Plant Breeder's Rights Act was passed, providing the legal framework for the collection of end‐point royalties (EPRs), now the primary source of funding for wheat‐breeding activities in Australia. Third, in 1999 the GRDC tendered for the development of three for‐profit public corporations that would invest revenues from EPRs to fund wheat breeding, allowing the GRDC to move upstream to focus on using its levy‐based funding for pre‐breeding research efforts. As of 2012, these breeding firms had each acquired a multinational private partner and had collectively reached the point where EPR revenues were sufficient to cover breeding costs. EPRs provide a very strong form of property rights for breeders such that producers will have to pay higher prices to access improved varieties, with some uncertainty about the extent to which those prices will be free to rise. Together, these three institutional innovations have created a well‐funded and well‐coordinated wheat research system that will enhance Australia's long‐run competitive position in the global grain market, but with an increasing burden of the costs of innovation borne by the industry.